A study on the feed value, in vitro digestibilities and methane production of tobacco (Nicotiana tabacum L.) field waste - Kilic, Unal; Kurt, Dursun; Aytac, Selim; Ayan, Ali Kemal (Progress in Nutrition, 2019)
This study aims to determine the nutrient contents, forage quality, in vitro true digestibility and methane production of the pellets prepared using straw and meal of tobacco (Nicotiana tabacum L.). Tobacco stalks (straws) and seeds collected from 25 different locations were used in this study. Daisy incubator was used to determine the in vitro true digestibility. In vitro gas production of the feed was determined using Hohenheim gas test while infrared methane analyzer was used to determine methane production. The study was designed in accordance with the completely randomized design. The results of the study showed that tobacco meal offers higher values in terms of crude protein and ether extract contents, while it offers lower ash, nitrogen free extract contents and cell wall fiber components when compared to tobacco straw (P